Balloon-Occluded Retrograde Transvenous Obliteration: Emergence as a Treatment for Gastric Varices and Medically Refractory Hepatic Encephalopathy - Chen, Ronnie C.; Lee, Edward Wolfgang; Cho, Sung Ki (Digestive Disease Interventions, 2017)
Gastric or esophageal variceal bleeding is a major complication of portal hypertension in patients with liver cirrhosis. Currently, liver transplant is still considered a gold standard treatment for gastric or esophageal variceal bleeding. What about varices associated with splenic vein thrombosis? In the United States and Europe, endoscopic treatment and transjugular intrahepatic portosystemic shunt (TIPS) have been considered as effective treatment options for these variceal bleeding. However, in South Korea and Japan, balloon-occluded retrograde transvenous obliteration (BRTO) has been considered as a well-accepted treatment option for the gastric variceal bleeding. In recent years, based on favorable outcomes of BRTO in Asia and unfavorable outcomes/complications of TIPS, BRTO has emerged as an alternative therapy for gastric varices in the Western world. In this review, we describe the indications/contraindications, techniques, and outcomes of BRTO.
Keywords: BRTO; gastric variceal bleeding; TIPS; hepatic encephalopathy